1999
DOI: 10.1177/089033449901500315
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Staphyloccocus Aureus Infected Sore Nipples: A Randomized Comparative Study

Abstract: Sore, cracked nipples are commonly experienced by breastfeeding mothers. We have previously reported a strong correlation between sore, cracked nipples and S. aureus colonization. A prospective, randomized clinical trial was performed to compare four treatment regimes for S. aureus infected sore nipples. Eighty-four breastfeeding mothers were enrolled in the study. After 5 days to 7 days of treatment, only 8% of mothers showed improvement in the "optimal breastfeeding technique alone" group, 16% improved with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 23 publications
0
63
0
3
Order By: Relevance
“…6 The study used a convenience sample of lactating women (n ϭ 26), assessed to be at risk for developing mastitis, who were then followed prospectively from the fifth day postpartum to the end of their lactation. Criteria used to identify "at-risk" mothers were based on previous research 7,8 and included one or a combination of the following: a history of mastitis in previous lactations, nipple trauma, attachment difficulties, and either an uncomfortable oversupply or engorgement at lactogenesis II. Reference samples of milk and 24-hour urine were collected from women at days 5, 14, 30, 60, and 90 postpartum, and blood at days 5 and 14, to obtain data on the normal range of a set of potential biochemical markers for mastitis.…”
Section: Methodsmentioning
confidence: 99%
“…6 The study used a convenience sample of lactating women (n ϭ 26), assessed to be at risk for developing mastitis, who were then followed prospectively from the fifth day postpartum to the end of their lactation. Criteria used to identify "at-risk" mothers were based on previous research 7,8 and included one or a combination of the following: a history of mastitis in previous lactations, nipple trauma, attachment difficulties, and either an uncomfortable oversupply or engorgement at lactogenesis II. Reference samples of milk and 24-hour urine were collected from women at days 5, 14, 30, 60, and 90 postpartum, and blood at days 5 and 14, to obtain data on the normal range of a set of potential biochemical markers for mastitis.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to the application of measurement instruments, seven publications used a previously developed instrument (9,15,17,19,(21)(22)25) ; however, only one of the clinical studies (9) reported its validity by means of the interobserver agreement index.…”
Section: Assessment Methods Of Nipple Traumamentioning
confidence: 99%
“…In only eight of the twenty publications (4)(5)(8)(9)(10)(11)(14)(15) , nipple trauma was defined; the concepts presented were similar in terms of disruption, lesion and injury to seven authors (5,(8)(9)(10)(11)(14)(15) . One author (4) presented a broader definition of nipple trauma, referring to the pathological change of the skin.…”
Section: Definition Of Nipple Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Policy makers, researchers, and professional organizations have pointed to the irrefutable benefits of breastfeeding for babies, mothers, society, and the environment (e.g., decreased health care costs, reduced acute and chronic illnesses, and mother-infant bonding). Unfortunately, as many as 96% of mothers (Graffy, 1992;Ziemer, Paone, Schupay, & Cole, 1990) experience sore, painful nipples during breastfeeding and stop nursing before they intended (Livingstone & Stringer, 1999).…”
mentioning
confidence: 99%